2013
DOI: 10.1111/nyas.12121
|View full text |Cite
|
Sign up to set email alerts
|

Just how important is spatial coincidence to multisensory integration? Evaluating the spatial rule

Abstract: This review addresses the question of when spatial coincidence facilitates multisensory integration in humans. According to the spatial rule (which was first formulated on the basis of neurophysiological data in anesthetized animals), multisensory integration is enhanced when stimuli in different sensory modalities are presented from the same spatial location. While the spatial rule fits with the available data from studies of overt and covert spatial attentional orienting, and from the majority of those studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
134
4
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(145 citation statements)
references
References 162 publications
(393 reference statements)
4
134
4
3
Order By: Relevance
“…Our findings corroborate previous research demonstrating that spatial coincidence plays a role in multisensory integration (Spence, 2013). In the present study, the higher proportion of correct responses in congruent as compared with incongruent trials, when pain-related information was shown, suggests that the visual system may dominate somatosensation when visual and tactile processing provide conflicting information (e.g., incongruent trials), or that vision may enhance sensitivity when providing similar information (e.g., congruent trials).…”
supporting
confidence: 82%
“…Our findings corroborate previous research demonstrating that spatial coincidence plays a role in multisensory integration (Spence, 2013). In the present study, the higher proportion of correct responses in congruent as compared with incongruent trials, when pain-related information was shown, suggests that the visual system may dominate somatosensation when visual and tactile processing provide conflicting information (e.g., incongruent trials), or that vision may enhance sensitivity when providing similar information (e.g., congruent trials).…”
supporting
confidence: 82%
“…By contrast, research on crossmodal (spatial) attentional control has focused primarily on bottom-up mechanisms, instead (Spence, 2013). The present study was therefore conducted in order to address this gap in the literature and to investigate whether top-down sets could also be applied in a multisensory task environment (involving visual and tactile stimulation).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the debate concerning the impact of top-down sets on attentional capture has been based on unimodal studies-that is, input from only a single sensory modality has been involved (see van der Lubbe & Van der Helde, 2006, for an exception-although these authors used an audiovisual task, all of the effects that were observed could be attributed to a supramodal spatial attention; see Spence, 2013, for a review of crossmodal spatial attention; see Spence, 2010, for a review of studies challenging the automaticity of crossmodal spatialcuing effects). The present study was designed to investigate whether top-down sets are as important for the guidance of crossmodal attention as they are for the guidance of visual selective attention (see Shore & Simic, 2005, for a study of top-down influences on visuotactile integration, resulting from variations in the proportion of congruent versus incongruent stimuli in a spatial visuotactile congruency task).…”
Section: Crossmodal Attention and Contingent Capturementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the importance of such coincidence seems to be task dependent. Particularly, spatial proximity seems to be relevant in tasks involving spatial attention and requiring orienting responses (see Spence, 2013 for a review).…”
Section: Question 3 How Much Does the Effect Of Attention Depend On mentioning
confidence: 99%